2021
DOI: 10.12659/ajcr.931665
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Optic Neuritis Associated with SARS-CoV-2 Infection: A Rare Complication

Abstract: Patient: Female, 21-year-old Final Diagnosis: Optic neuritis Symptoms: Vision changes Medication:— Clinical Procedure: — Specialty: Infectious Diseases • Neurology Objective: Rare co-existance of disease or pathology Background: Since the outbreak of the SARS-CoV-2 infection, extensive research has been conducted on the pulmonary implications of this novel disease. However, there has been limited da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 10 publications
(13 reference statements)
0
32
0
1
Order By: Relevance
“…Although they have been more frequently described with the SARS-CoV-2 infection, they are already well known to occur after COVID-19 vaccination. Previous cases of ischemic optic neuropathy have also been reported in patients with COVID-19 [ 21 26 ]. Recently, Al-Mayhani et al [ 2 ] also described VITT characteristics with arterial thrombosis; they reported 3 cases of ischemic stroke associated with COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 96%
“…Although they have been more frequently described with the SARS-CoV-2 infection, they are already well known to occur after COVID-19 vaccination. Previous cases of ischemic optic neuropathy have also been reported in patients with COVID-19 [ 21 26 ]. Recently, Al-Mayhani et al [ 2 ] also described VITT characteristics with arterial thrombosis; they reported 3 cases of ischemic stroke associated with COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 96%
“…Complaints associated with SARS-CoV-2 infection include pain, redness, and photophobia, suggesting probable eye surface disease. We found no papers that analyzed the possibility that the patient could have had a paucisymptomatic SARS-CoV-2 initial infection, and that the eye involvement eventually led to the diagnosis of PIMS-TS [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…There have been countless reports of ocular and neurological complications since the onset of the coronavirus pandemic [2,[20][21][22][23][24]28]. The neuro-ophthalmological symptoms are considered to represent a separate entity of COVID-19 related manifestations, with multiple underlying mechanisms, such as the high affinity for ACE2 receptors, whose existence in the eye, nerves and vascular endothelium has already been demonstrated [2][3][4][5]7,16,17,[25][26][27][28][30][31]. In this case, the panuveitis could be a feature of PIMS temporally associated with SARS-CoV-2 infection, but this remains a hypothesis and warrants further investigations and follow-up due to the risk of vision loss and the association with systemic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…”Visual loss” in COVID-19 patients was reported in a few articles. Nonetheless, it has been observed that its onset may be due to viral neurotropism and indirect immunologic and neurovascular effects [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%